The Effects of Regulation, Literacy and Promotion in the Development of the Halal Industrial Ecosystem through Sharia Financing In West Nusa Tenggara - Yuke Rahmawati; Aini Masruroh; Sanurdi (International Journal of Management, Economic and Accounting, 2026)
This study aims to comprehensively analyze the development of the halal industrial ecosystem in West Nusa Tenggara Province, as one of the halal tourism destinations in Indonesia. The West Nusa Tenggara Regional Government has issued Regional Regulation Number 2 of 2016 on Halal Tourism, as a derivative of Law Number 10 of 2009 on Tourism and Law Number 33 of 2014 on the Guarantee of Halal Products. In the context of developing the halal industry, there are several variables that are important to study, including regulation, halal industry literacy, promotion of halal tourist destinations, and support for sharia financing access to the halal industry ecosystem. To this end, the study applies a descriptive quantitative method with path analysis (SEM test) using intervening variables. This study found that the regulatory aspects were not significant or had no direct effect on the halal industry, while literacy and promotion had a significant direct effect on the halal industry. As for the indirect effect, regulation (regional) does not indirectly affect the halal industry, while literacy and promotion indirectly have a significant effect on the development of the halal industry ecosystem. Lastly, Islamic financing has a significant direct effect on the halal industry. The findings of this study are expected to be able to provide policy recommendations for local and central governments in the development of the halal industry ecosystem.